The Independent Church of God of the Juda Tribe of Israel: The Black Jews : As a fade from black to pure white - Cook, Allan Wilson, 1872-1935; Winston, Robert W. (Robert Watson), 1860-1944 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Independent Church of God of the Juda Tribe of Israel: The Black Jews" by Bishop A.W. Cook is a religious and sociopolitical publication written in the early 20th century. The book discusses the identity and experiences of Black Jews, advocating for recognition of their heritage and the struggles faced by the Black community. It aims not only to document the history of the Black Jews but also to propose a vision for their future and regeneration. The opening of the book introduces the Independent Church of God and its foundational beliefs, emphasizing a united vision among all people. It details the church's constitution, its aims to uplift the community, and a brief autobiography of the author, showcasing his journey and spiritual mission. Additionally, it outlines a series of subjects relevant to the Black community, including the historical treatment of Black Jews, contemporary issues of racial identity, and calls for economic empowerment and unity among Black people. The tone is both prophetic and instructional, urging readers to recognize their heritage while calling for social and spiritual awakening. (This is an automatically generated summary.)
Release date is 2022-08-11
Mary Glenn Krause, Thomas Frost and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive).
Keywords: African Americans -- Colonization -- Africa; Southern States -- Race relations; Black Hebrews